2020
DOI: 10.26686/wgtn.13019450.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Feng-Shui and CFD: Analyzing natural ventilation and human comfort

Abstract: No description supplied

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…The traditional vernacular knowledge includes the more known aspects of Feng-shui. The previous research by Li et al (Li et al, 2020) has confirmed that Lingnan's vernacular knowledge is still being used today. In their research, virtual building simulations have been employed to validate the recommendations given in vernacular wisdom.…”
Section: Discussion Summarymentioning
confidence: 71%
See 1 more Smart Citation
“…The traditional vernacular knowledge includes the more known aspects of Feng-shui. The previous research by Li et al (Li et al, 2020) has confirmed that Lingnan's vernacular knowledge is still being used today. In their research, virtual building simulations have been employed to validate the recommendations given in vernacular wisdom.…”
Section: Discussion Summarymentioning
confidence: 71%
“…Vernacular knowledge for architectural design existed in China for thousands of years (Li et al, 2020). The considerations for forming the best-integrated effect include wind, thermal, acoustic, light environment and other parameters.…”
Section: Introductionmentioning
confidence: 99%